Penentuan Channel Menggunakan Atribut Spectral Decomposition Pada Data Seismik 3D Parihaka, Cekungan Taranaki, New Zealand (UPEJ Unnes Physics Education Journal, 2023)
The channel is the most likely place containing hydrocarbons, oil and petroleum. The research aims to determine the presence of a channel and a geological feature channel using dectional 3D properties on the seismic 3D field of Parihaka, Taranaki Basin, New Zealand. Identification Channel and geological features are done using software Schlumberger Petrel 2017 for data interpretation. Data interpretation is picking, horizon, the construction of time structure maps and the building of maps surface attributes using spectral deactivation attributes. Spectral Decomposition use of frequency 35 Hz, 40 Hz, 45 Hz, 50 Hz, 55 Hz, and 60 Hz. In this study, there are two major channels: channel 1 and channel 2. Some of the geological features were also found using Spectral Decomposition attributes such as meandering channels, point bars, cut bank, channel edge, sand, and shale on those 2 channels.